(untitled) (Proceedings of Southern Federal University. Philology, 2015)
Tabachenko Lyudmila Vladimirovna Positional verbs стояти, chdhmu, лежати in the Russian language of XI- XVII centuries are much broader than in the modern Russian language, were used in the spatial meaning of “пребывать, находиться где-л.”, indicating the location of living beings, inanimate objects, two-dimensional objects, administrative units. At the cognitive level, such properties of the subject, such as animation, mentality, sociality, the presence of goal-setting, enable the transfer situation from definite-spatial plan (to be where) to the social plan, that is the source of certain transformations of generally location semantics to ‘располагаться на каком-л. участке местности для ведения боевых действий’, ‘осаждать’, ‘постоянно жить где-л.’ When the functional interchangeability of positional verbs retain individual semantic nuances: стояти contains the seme ‘быть готовым к военным действиям’ (based on the component ’to be in the upright position on your feet’), which later will be developed in the seme ’functionality’; лежати on the one hand, focuses the subject in a noun-set of semantics, on the other - massiveness of semantics, that can spread, covering some surface; сhдhтu traditionally was used to mean ‘постоянно быть на одном месте’, and in this example it is focused the sema of prolonged staying. Key words: history of the Russian language, positional verbs, spatial meanings.